Il “tutto” dell’uomo. Una rilettura di Qo 12,8-14 - Voltaggio, Francesco Giosuè (Liber Annuus, 2024)
Abstract This paper offers a detailed exegesis of the epilogue of the book of Ecclesiastes (12:9-14), with special attention to the most debated points regarding its interpretation. Such an exegesis makes it possible to address the long-standing question regarding the redaction of the passage and to assess whether this is the work of an epilogist who wanted to correct or at least mitigate the most problematic or “scandalous” aspects of the book with the intention of bringing it back into the mainstream of Israel’s traditional wisdom, as is the opinion of a good number of exegetes. Such a pre-understanding often guides such exegetes in the interpretation of the passage’s most difficult expressions. Although it is difficult to determine whether the epilogue of Ecclesiastes is the work of another hand, on the basis of the exegesis we have offered, supported by various recent studies, it must be concluded, contrary to the above opinion, that the epilogue, far from being in dissonance with the whole book, should be read in its light and, in turn, illuminates the deep intent of the whole work.